Formative Peer Feedback On Undergraduate Students’ Speaking Ability - Erniyanti Nur Fatahhela Dewi; Nidyah Hasanah; Muhammad Faishol Nurul Huda (Al-Lisan: Jurnal Bahasa, 2020)
This descriptive qualitative study investigated the undergraduate students' perception in public speaking class that conducted formative peer feedback, especially for undergraduate students who learned the subject at State Islamic University Jakarta. This study revealed the undergraduate students’ perception about the implementation of formative peer feedback in assessing their formative public speaking class. Besides, the authors provided an open-ended questionnaire and semi-structured interview to know how applicable the formative peer feedback for undergraduate students, which part that students interested in when they assess their friends, and identify students’ feelings when used the formative peer feedback in public speaking class. Concerning the results of the study, the writers discovered that formative peer feedback is very beneficial for the undergraduate student in the learning process of the public speaking class. While doing the assessment, most undergraduate students seem more interested in assessing their peer's body language and speech content. In addition, the result that the writers got from the investigation was 62.5% that claimed their peer’s feedback was very objective. Other than that, when using the formative peer feedback in the public speaking class, 65.6% of undergraduate learners were feeling satisfied.